A Novel Role for CSRP1 in a Lebanese Family with Congenital Cardiac Defects - Kamar, Amina; Fahed, Akl C.; Shibbani, Kamel; El-Hachem, Nehme; Bou-Slaiman, Salim; Arabi, Mariam; Kurban, Mazen; Seidman, Jonathan G.; Seidman, Christine E.; Haidar, Rachid; Baydoun, Elias; Nemer, Georges; et al. (Frontiers in Genetics, 2017)
Despite an obvious role for consanguinity in congenital heart disease (CHD), most studies fail to document a monogenic model of inheritance except for few cases. We hereby describe a first-degree cousins consanguineous Lebanese family with 7 conceived children: 2 died in utero of unknown causes, 3 have congenital heart disease, and 4 have polydactyly. The aim of the study is to unveil the genetic variant(s) causing these phenotypes using next generation sequencing (NGS) technology. Targeted exome sequencing identified a heterozygous duplication in CSRP1 which leads to a potential frameshift mutation at position 154 of the protein. This mutation is inherited from the father, and segregates only with the CHD phenotype. The in vitro characterization demonstrates that the mutation dramatically abrogates its transcriptional activity over cardiac promoters like NPPA. In addition, it differentially inhibits the physical association of CSRP1 with SRF, GATA4, and with the newly described partner herein TBX5. Whole exome sequencing failed to show any potential variant linked to polydactyly, but revealed a novel missense mutation in TRPS1. This mutation is inherited from the healthy mother, and segregating only with the cardiac phenotype. Both TRPS1 and CSRP1 physically interact, and the mutations in each abrogate their partnership. Our findings add fundamental knowledge into the molecular basis of CHD, and propose the di-genic model of inheritance as responsible for such malformations.